ARAHAN DESAIN RUANG KOTA PERSINGGAHAN (SHUKUBAMACHI) KOTA FUTAGAWA, PROPINSI AICHI, JEPANG - , Radiaswari, ST ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Shukubamachi flourished during Edo period, between 2 existing capital city, The new capital of Edo (later renamed Tokyo) and The former capital of Kyoto. Shukubamachis are transit/post towns accomodating travelers between these two capital cities. Five major routes can be found, within 2 main corridors, The Tokaido route, and The Nakasendo route. Shukubamachis in Tokaido route growth more vibrant in result of the better road condition and existing accommodation provided. Futagawa-juku (now Futagawa-chou) in Tokaido route was one of these convenient transit town (shukubamachi). However, after Edo period, urban growth developed slowly, until it became stagnant. This stagnant growth had caused the insignificant change to urban space in shukubamachis. Contrast to the new growth, the old houses in the older part of Futagawa town (along The Old Tokaido Road) were mostly unoccupied and deserted. Since 2002 Futagawa town begin to improve themselves in order to create a better living space that nurture the existing shukubamachi character fit in the future development of the town. This research try to analyze the formation of uban space in Futagawa through 3 step: (1) identifying Futagawa urban space formation during Edo premodern period and today, (2) finding its urban space transformation, and (3) determining design guideline fit for Futagawa future urban development. Deductive-rasionalistic method is used to extract the main issue of Futagawa urban space into 3 major topic, urban components, urban configuration, and urban function. Research findings are used to determine design guideline of urban space in Futagawa town which will support the continuity of Futagawa old town along The Tokaido old route.